Prognostic Significance of Preterm Isolated Decreased Fetal Movement - Karahanoğlu, Ertuğrul; Altınboğa, Orhan; Akpınar, Funda; Özdemirci, Şafak; Baser, Emre; Aktaş, Yıldız; Yalvaç, Serdar (Gynecology Obstetrics & Reproductive Medicine, 2017)
Objective: Our aim is to evaluate the prognostic significance of isolated, preterm decreased fetal movement following normal initial full diagnostic workup. Study design: A retrospective observational study was conducted at a tertiary centre. The applied protocol was approved by the Medical Research Ethics Department of the hospital where the research was conducted. Obstetrics outcomes of preterm- and term-decreased fetal movement were compared following an initial, normal diagnostic work up. Evaluated outcomes were birth weight, mode of delivery, stillbirth rate, induction of labour, development of gestational hypertension, small for gestational age and oligohydramnios, polyhydramnios during the follow up period. Result: Obstetric complications related to placental insufficiency develops more frequently for decreased fetal movement in preterm cases with respect to that of in term cases. Following the diagnosis of decreased fetal movement, pregnancy hypertension occurred in 17% of preterm decreased fetal movement cases and in 4.7% of term decreased fetal movement cases. Fetal growth restriction developed in 6.6% of preterm decreased fetal movement and in 2.3% of term decreased fetal movement. Amniotic fluid abnormalities more frequently developed in preterm decreased fetal movement. Conclusion: Following an initial normal diagnostic workup, preterm decreased fetal movement convey a higher risk for the development of pregnancy complications associated with placental insufficiency. The patient should be monitored closely and management protocols must be developed for initial normal diagnostic workups in cases of preterm decreased fetal movement.